Molecular patterns in the evolution of serrated lesion of the colorectum. Issue 8 (17th October 2012) - Gaiser, Timo; Meinhardt, Sandra; Hirsch, Daniela; Killian, Jonathan Keith; Gaedcke, Jochen; Jo, Peter; Ponsa, Immaculada; Miró, Rosa; Rüschoff, Josef; Seitz, Gerhard; Hu, Yue; Camps, Jordi; et al.
Abstract Colorectal cancer (CRC) mostly develops from a variety of polyps following mainly three different molecular pathways: chromosomal instability (CIN), microsatellite instability (MSI) and CpG island methylation (CIMP). Polyps are classified histologically as conventional adenomas, hyperplastic polyps, sessile serrated adenomas/polyps (SSA/P) and traditional serrated adenomas (TSA). However, the association of these polyps with the different types of CRCs and the underlying genetic and epigenetic aberrations has yet to be resolved. In order to address this question we analyzed 140 tumors and 20 matched mucosae by array comparative genomic hybridization, by sequence analysis of the oncogenes BRAF, KRAS, PI3K3CA and by methylation arrays. MSI was tested indirectly by immunohistochemistry (IHC) and a loss of MLH1, MSH2, MSH6 or PMS2 was assigned as high microsatellite instability (MSI‐H), while low microsatellite instability (MSI‐L) was defined as MGMT IHC negativity only. CIN was detected in 78% of all MSI‐H CRCs, most commonly as a gain of chromosome 8. Methylation data analyses allowed classification of samples into four groups and detected similar methylation profiles in SSA/P and MSI‐H CRC. TSA also revealed aberrant methylation pattern, but clustered more heterogeneously and closer to microsatellite stable (MSS) CRCs. SSA/P, TSA and MSI‐H CRCs had the highest degree of promotor methylation (CIMP pathway). Chromosomal instability, in contrast to the established doctrine, is a common phenomenon in MSI CRCs, yet to a lower extent and at later stages than in MSS CRCs. Methylation analyses suggest that SSA/P are precursors for MSI‐H CRCs and follow the CIMP pathway.